Uterine luminal fluid protein content in viable and non-viable Conceptuses in sheep - Rodríguez Márquez, José; Hernández, Aureliano; Vera, Víctor; Morales, Roneisa (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
During implantation, embryo survival depends on the availability of uterine and/or trophoblastic secreted molecules, including proteins. In order to determine possible differences in the protein profile of the uterine luminal fluid (ULF) adjacent to the embryonic site of viable and non-viable conceptuses at 20, 28 and 35 days of gestation, two-dimensional (2D) PAGE electrophoresis was carried out. The ULF adjacent to viable conceptuses, had greater amounts of proteins as compared to correspondent sites of non-viable conceptuses. In all the studied gestational period there were several proteins in the ULF near viable embryos, which were absent in the corresponding areas of the non viable ones. Two of these proteins were identified. One corresponds to transferrin, which can be produced either by the conceptus or the mother. It is important for proliferation, differentiation, and cellular function, since it is an iron transporting and binding molecule. Its absence in the ULF near non viable embryos might be interpreted as a lack of production by the conceptus. Likewise, transferrin appears to be involved in the formation of blood vessels, which then could account for the absence of those structures in the membranes of non viable conceptuses. The other protein corresponds to aldose reductase, which is responsible for sorbitol and fructose synthesis, although its metabolic role during implantation is still unknown. In conclusion, some proteins present near viable embryos are absent in non viable conceptuses at days 20; 28 and 35 of gestation which could be indicators to determine, at least partially, embryonic survival during the studied period.